The REpeated ASSEssment of SurvivorS in intracerebral haemorrhage: protocol for a multicentre, prospective observational study - Daniel Woo; Richard Thompson; Carl D Langefeld; Nichol McBee; Daniel Hanley; Matthew L Flaherty; Lauren Sansing; Karen Lane; Lee A Gilkerson; Achala Vagal; Nathan Walborn; Wendy Ziai; et al. (BMJ Open)
Background The REpeated ASSEssment of SurvivorS (REASSESS) study will conduct long-term cognitive, functional and neuropsychiatric performance assessments to determine whether evacuation of spontaneous intracerebral haemorrhage (ICH) reduces the risk of later cognitive decline in the ageing brain.Methods and analysis This study will compare rates of cognitive decline under two treatment strategies for ICH. The first strategy is the use of minimally invasive surgery (MIS) with similar techniques as performed in (1) the Minimally Invasive Surgery plus rt-PA in the Treatment of Intracerebral haemorrhage Evacuation phase III (MISTIE III) trial, (2) the Early MiNimally-invasive Removal of IntraCerebral Haemorrhage (ENRICH) trial and (3) a single-centre cohort of consecutively treated patients with MIS. The second strategy is the current non-surgical standard of care using data from controls in MISTIE III and ENRICH and comparative data from The Ethnic/Racial Variations of ICH (ERICH) studyextended into the ERICH-Longitudinal study, which followed over 900 of ERICH cases with serial cognitive examinations. If successful, the REASSESS study could demonstrate that reduction of ICH volume is a critical target to reduce the risk of progressive cognitive decline, establish targets for residual haematoma volume reduction and determine if greater residual haematoma volume leads to a long-term inflammatory state.Ethics and dissemination Approval of this study was obtained from the Johns Hopkins University Institutional Review Board (IRB00311985). The findings of the study will be published in academic peer-reviewed journals.Trial registration number NCT05611918; ClinicalTrials.gov; registered on 23 May 2023.